The Effectiveness of Problem-Based Learning Assisted by Powtoon Media on the Activeness and Learning Outcomes of Pancasila Education in 4th-Grade Elementary School Students - Faradina Hibatul Haqqi; Kurotul Aeni; Raed Abdullah Albalushi (Al Ibtida: Jurnal Pendidikan Guru MI, 2025)
Abstract Low learning outcomes and student engagement result from ineffective learning models and media in actively involving students. This study analyzes the effectiveness of the problem-based learning (PBL) model combined with Powtoon media in enhancing student participation and learning outcomes. A quantitative method with a quasi-experimental design was used, involving 4th-grade elementary students divided into an experimental class (IV A, 33 students) and a control class (IV B, 30 students) using a conventional model. Engagement data were collected through observation, and learning outcomes were assessed via evaluation tests. Data analysis used SPSS 26 with normality, homogeneity, t-test, N-Gain, and engagement score tests. The results showed a significant t-test value of 0.000 < 0.05, indicating a significant difference in engagement and learning outcomes between the two groups. The N-Gain percentage was 61% (moderately effective) in the experimental class and 43% (less effective) in the control class. The highest engagement category in the experimental class was visual activities (87.87%), while in the control class, it was mental activities. These findings demonstrate that the PBL model combined with Powtoon media effectively enhances student engagement and learning outcomes.Keywords: problem-based learning, Powtoon media, activeness, and learning outcomes.AbstrakRendahnya capaian pembelajaran dan keterlibatan siswa disebabkan oleh model dan media pembelajaran yang kurang efektif dalam melibatkan siswa secara aktif. Penelitian ini menganalisis efektivitas model pembelajaran berbasis masalah (PBL) yang dipadukan dengan media Powtoon dalam meningkatkan partisipasi dan capaian pembelajaran siswa. Metode kuantitatif dengan desain quasi eksperimen digunakan, melibatkan siswa SD kelas 4 yang dibagi menjadi kelas eksperimen (IV A, 33 siswa) dan kelas kontrol (IV B, 30 siswa) dengan menggunakan model konvensional. Data keterlibatan dikumpulkan melalui observasi, dan capaian pembelajaran dinilai melalui tes evaluasi. Analisis data menggunakan SPSS 26 dengan uji normalitas, homogenitas, uji-t, N-Gain, dan skor keterlibatan. Hasil penelitian menunjukkan nilai uji-t signifikan sebesar 0,000 < 0,05, yang menunjukkan adanya perbedaan yang signifikan dalam keterlibatan dan capaian pembelajaran antara kedua kelompok. Persentase N-Gain sebesar 61% (cukup efektif) pada kelas eksperimen dan 43% (kurang efektif) pada kelas kontrol. Kategori keterlibatan tertinggi pada kelas eksperimen adalah aktivitas visual (87,87%), sedangkan pada kelas kontrol adalah aktivitas mental. Temuan ini menunjukkan bahwa model PBL yang dikombinasikan dengan media Powtoon efektif meningkatkan keterlibatan dan hasil belajar siswa.Kata kunci: pembelajaran berbasis masalah, media Powtoon, keaktifan, dan hasil belajar.